Your undergraduate dissertation : the essential guide for success - Walliman, Nicholas S. R. (Los Angeles : SAGE, 2014)
This guide to all the essential facets of dissertation writing at un dergraduate level provides advice for preparing a project and choosing a topic, and guidelines for writing a project proposal and producing a literature review.
Includes bibliographical references (pages 275-276) and index.
Keywords: Dissertations, Academic; Academic writing